Copper cobalt tin sulphide (Cu2CoSnS4) anodes synthesised using a chemical route for stable and efficient rechargeable lithium-ion batteries. Issue 38 (8th September 2022) - Inamdar, Akbar I.; Hou, Bo; Chavan, Harish S.; Salunke, Amol S.; Han, Jonghoon; Shin, Giho; Park, Sunjung; Yeon, Seungun; Shrestha, Nabeen K.; Im, Hyunsik; Kim, Hyungsang
Abstract : We demonstrate a lithium-ion battery performance with a novel Cu2 CoSnS4 anode prepared by a hydrothermal method. It exhibits a specific capacity of 198.7 mA h g −1, 83% coulombic efficiency, excellent rate capability and capacity retention. Abstract : In everyday life, superior lithium-ion batteries (LIBs), with fast charging ability, have become valuable assets. The LIB performance of an anode composite copper cobalt tin sulphide (Cu2 CoSnS4 ; CCTS) electrode, which was fabricated using a simple and easy hydrothermal method, was investigated. The electrochemical charge storage performance of the CCTS anode demonstrated sustainability, high-rate capability and efficiency. The CCTS anode exhibited a first discharge capacity of 914.5 mA h g −1 and an average specific capacity of 198.7 mA h g −1 in consecutive cycles at a current density of 0.1 A g −1 . It had a capacity retention of ∼62.0% and a coulombic efficiency of more than 83% after over 100 cycles, demonstrating its excellent cycling performance and reversibility. It can be an alternative anode to other established electrode materials for real battery applications.